2017
DOI: 10.1016/j.celrep.2017.03.079
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analyses Reveal the Influence of Geographic Origin, Migration, and Hybridization on Modern Dog Breed Development

Abstract: There are nearly 400 modern domestic dog breeds with a unique histories and genetic profiles. To track the genetic signatures of breed development, we have assembled the most diverse dataset of dog breeds, reflecting their extensive phenotypic variation and heritage. Combining genetic distance, migration, and genome-wide haplotype sharing analyses, we uncover geographic patterns of development and independent origins of common traits. Our analyses reveal the hybrid history of breeds and elucidate the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
511
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 335 publications
(539 citation statements)
references
References 43 publications
22
511
3
3
Order By: Relevance
“…However, haplotypes would be broken down over time by recombination, so haplotype sharing reflects recent genetic contact only. In fact, haplotype sharing relies on large haplotype size that particularly targets regions that are shaped by admixture (Parker et al, ). These two phenomena explain why we detect only a modest correlation between the two similarity matrices.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, haplotypes would be broken down over time by recombination, so haplotype sharing reflects recent genetic contact only. In fact, haplotype sharing relies on large haplotype size that particularly targets regions that are shaped by admixture (Parker et al, ). These two phenomena explain why we detect only a modest correlation between the two similarity matrices.…”
Section: Methodsmentioning
confidence: 99%
“…Given the large number of processes involved and the relatively poor and sometimes unreliable historical documentation of the creation of dog breeds in the distant past, until now it has been difficult to reconstruct the complex evolutionary relationships among breeds. However, recent analyses of genome sequences have permitted separating signatures of shared ancestry from that of recent admixture and revealed that the dogs’ evolutionary history can be characterized by a two‐step process (Lindblad‐Toh et al, ; Parker et al, ; Wang et al, ). First, an ancient separation of major breed types may have occurred, through which features of appearance and behaviour have been selected to enhance the desired main function in accordance with the human progression (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Some statistical evidence suggests that Asian and Middle Eastern varieties diverged long before what has been called the 'Victorian Explosion' of dog breeds in Britain and the rest of Europe (Parker et al, 2017). One such study identified 9 dog breeds that could be represented on the outgroup of a broad-scale inter-species phylogeny (Pollinger et al, 2010 single nucleotide polymorphisms that gave a genome-wide coverage of 912 dogs representing 85 breeds.…”
Section: Unrooted Treesmentioning
confidence: 99%
“…One such study identified 9 dog breeds that could be represented on the outgroup of a broad-scale inter-species phylogeny (Pollinger et al, 2010 single nucleotide polymorphisms that gave a genome-wide coverage of 912 dogs representing 85 breeds. Among the oldest lineages of European descent were those most closely related to herding breeds, mastiffs, and other hound varieties (Parker et al, 2017& Pollinger et al, 2010.…”
Section: Unrooted Treesmentioning
confidence: 99%
See 1 more Smart Citation